CONSTRUCTION AND PERFORMANCE EVALUATION OF TWO STAGED THREE BLADED SAVONIUS VERTICAL AXIS WIND ENERGY CONVERSION SYSTEM - Ohaji, Denis E.; Musa, M.; Momoh, M.; Akpootu, D. O.; Bello, G. (FUDMA JOURNAL OF SCIENCES, 2023)
This study is intended to increase the rotor performance of the Savonius wind rotor, by increasing the numbers of blades of the already existing two blades Savonius vertical axis wind turbines (VAWTs) to three which was designed to increase the Savonius wind rotor performance. Two stage three bladed wind turbine system has been designed and constructed. The system was made up of six split drums which were welded together to form a concave shape to capture wind from all directions, with a shaft to pass through the midst of the welded drums which was then mounted on a tower of about 15 m high, which in turn will cause the rotor to rotate. This was then connected to a 12 V Generator. The wind turbine converts the kinetic energy available in the wind to produce electricity, using the Generator with output power of 60 W. The results obtained showed that the system was able to accept wind from any direction and commenced rotation as soon as the wind speed of 3.3 m/s (cut in) was available at the site. The minimum and maximum power outputs of 5.14 W and 13.34 W, corresponding to wind speeds of 7.2 m/s and 9.4.5 m/s were recorded respectively. Similarly, for a rotation per minute of 811 rpm a voltage of 7.14 V was generated. Hence for a two stages three blades Savonius the performance was 12.2 %, as against a single stage two blades Savonius whose performance was 7%, a deviation of 5.2 %.
Keywords: Horizontal axis wind turbine; kinetic energy; Savonius wind Rotor; Torque; wind power